Medical decision in COPD: the evidence-based history - Duarte-de-Araújo, António (2021)
Randomized controlled trials together with systematic reviews and meta-analyses have been the cornerstone of clinical research. Some studies, because of the size of the sample, the use of randomization and well-defined measurements, the participation of multiple institutions, or long-term follow-up, are able to give a significant level of evidence. We chronologically describe and comment on a group of trials on chronic obstructive pulmonary disease (COPD) that have significantly influenced the scientific and medical community in understanding and managing the disease in the first years of the XXI century. They contributed to the different versions of the GOLD strategy.